Top Gun : Maverick [videorecording (Blu-Ray)] - Cash, Jim; Epps, Jack (Paramount, 2022)
After more than 30 years of service as one of the navy's top aviators, Pete 'Maverick' Mitchell is where he belongs, pushing the envelope as a courageous test pilot and dodging the advancement in rank that would ground him. Training a detachment of graduates for a special assignment, Maverick must confront the ghosts of his past and his deepest fears, culminating in a mission that demands the ultimate sacrifice from those who choose to fly it.